Discovering our past: a history of the United States - Appleby, Joyce Oldham; Brinkley, Alan; Broussard, Albert S.; McPherson, James M.; Ritchie, Donald A. (McGraw-Hill networks, 2018)
The first Americans -- Exploring the Americas -- Colonial America -- Life in the American colonies -- The spirit of independence -- The American Revolution -- A more perfect union -- The Constitution -- The Federalist era -- The Jefferson era -- Growth and expansion -- The Jackson era -- Manifest destiny -- North and south -- The spirit of reform -- Toward civil war -- The Civil War -- The Reconstruction era -- Opening the West -- The industrial age -- An urban society -- The Progressive Era -- Rise to world power -- World War I -- The jazz age -- The depression and the New Deal -- America and World War II -- The Cold War Era -- The Civil Rights Era -- The Vietnam Era -- A troubled nation -- New challenges